Improved thermal stability of Nd-Ce-Fe-B sintered magnets by Y substitution. (1st April 2017) - Peng, Baixing; Ma, Tianyu; Zhang, Yujing; Jin, Jiaying; Yan, Mi
Abstract: To improve the thermal stability of the Nd-Ce-Fe-B sintered magnets, Y was incorporated via the binary main phase (BMP) approach. At the same substitution level for Nd (9 wt%), the absolute value of the coercivity temperature coefficient from 293 to 393 K for the Nd-Ce-Y-Fe-B magnet is 16.2% lower than that for the Nd-Ce-Fe-B one. This is attributed to the weakened temperature dependence of the magnetocrystalline anisotropy field and the magnetization as Y preferably enters into the 2:14:1 phase. It suggests that Y and Ce co-substitution for Nd is appealing to prepare low-cost RE-Fe-B permanent magnets with improved thermal stability. Graphical abstract: